Sex-Steroid Regulation of Relaxin Receptor Isoforms (RXFP1 & RXFP2) Expression in the Patellar Tendon and Lateral Collateral Ligament of Female WKY Rats - Dehghan, F.; Muniandy, S.; Yusof, A. (Ivyspring International Publisher, 2014)
The incidence of non-contact knee injury was found higher in female than in male and is related to the phases of the menstrual cycle. This raised the possibility that female sex-steroids are involved in the mechanism underlying this injury via affecting the expression of the receptors for relaxin, a peptide hormone known to modulate ligament laxity. Therefore, this study aims to investigate the effect of sex-steroids on relaxin receptor isoforms (RXFP1 & RXFP2) expression in the ligaments and tendons of the knee. Methods: Ovariectomized adult female WKY rats were treated with different doses of estrogen (0.2, 2, 20 μg/kg), progesterone (4mg) and testosterone (125 & 250μg/kg) for three consecutive days. At the end of the treatment, the animals were sacrificed and the patellar tendon and lateral collateral ligament were harvested for mRNA and protein expression analyses by Real Time PCR and Western blotting respectively. Results: RXFP1, the main isoform expressed in these knee structures and RXFP2 showed a dose-dependent increase in expression with estrogen. Progesterone treatment resulted in an increase while testosterone caused a dose-dependent decrease in the mRNA and protein expression of both relaxin receptor isoforms. Discussion: Progesterone and high dose estrogen up-regulate while testosterone down-regulates RXFP1 and RXFP2 expression in the patellar tendon and lateral collateral ligament of rat's knee. Conclusion: Relaxin receptor isoforms up-regulation by progesterone and high dose estrogen could provide the basis for the reported increase in knee laxity while down-regulation of these receptor isoforms by testosterone could explain low incidence of non-contact knee injury in male.